Gait Stability Training in a Virtual Environment Improves Gait and Dynamic Balance Capacity in Incomplete Spinal Cord Injury Patients - van Dijsseldonk, Rosanne B.; de Jong, Lysanne A. F.; Groen, Brenda E.; Vos-van der Hulst, Marije; Geurts, Alexander C. H.; Keijsers, Noel L. W. (Frontiers in Neurology, 2018)
Many patients with incomplete spinal cord injury (iSCI) have impaired gait and balance capacity, which may impact daily functioning. Reduced walking speed and impaired gait stability are considered important underlying factors for reduced daily functioning. With conventional therapy, patients are limited in training gait stability, but this can be trained on a treadmill in a virtual environment, such as with the Gait Real-time Analysis Interactive Lab (GRAIL). Our objective was to evaluate the effect of 6-weeks GRAIL-training on gait and dynamic balance in ambulatory iSCI patients. In addition, the long-term effect was assessed. Fifteen patients with chronic iSCI participated. The GRAIL-training consisted of 12 one-hour training sessions during a 6-week period. Patients performed 2-minute walking tests on the GRAIL in a self-paced mode at the 2nd, and 3rd (baseline measurements) and at the 12th training session. Ten patients performed an additional measurement after 6 months. The primary outcome was walking speed. Secondary outcomes were stride length, stride frequency, step width, and balance confidence. In addition, biomechanical gait stability measures based on the position of the center of mass (CoM) or the extrapolated center of mass (XCoM) relative to the center of pressure (CoP) or the base of support were derived: dynamic stability margin (DSM), XCoM-CoP distance in anterior-posterior (AP) and medial-lateral (ML) directions, and CoM-CoP inclination angles in AP and ML directions. The effect of GRAIL-training was tested with a one-way repeated measures ANOVA (α=0.05) and post-hoc paired samples t-tests (α=0.017). Walking speed was higher after GRAIL training (1.04m/s) compared to both baseline measurements (0.85m/s and 0.93m/s) (p<.001). Significant improvements were also found for stride length (p<.001) and stability measures in AP direction (XCoM-CoPAP (p<.001) and CoM-CoPAP-angle (p<.001)). Stride frequency (p=.27), step width (p=.19), and stability measures DSM (p=0.06), XCoM-CoPML (p=.97) and CoM-CoPML-angle (p=.69) did not improve. Balance confidence was increased after GRAIL training (p=.001). The effects were remained at 6 months. Increased walking speed, stride length, AP gait stability , and balance confidence suggest that GRAIL-training improves gait and dynamic balance in patients with chronic iSCI. In contrast, stability measures in ML direction did not respond to GRAIL-training.